Bone-specific median age of hand-wrist maturation from Sudan - Fadil Elamin; Hassan Yahya Hassan Mohamed; Nihal Abdelazeem; Ahmed Elamin; Helen M. Liversidge (Taylor & Francis Group, 2023)
Background Maturation of bones in the hand-wrist region varies among individuals of the same age and among world groups. Although some studies from Africa report differences to other ethnic groups, the lack of detailed bone-specific maturity data prevents meaningful comparisons. Aim The aim of this study was to describe bone-specific maturity for developing hand-wrist bones in individuals in Khartoum, Sudan. Subjects and methods The sample was selected from healthy patients attending a dental hospital in Khartoum with known age and ancestry (males = 280, females = 330; aged between 3 and 25 years). Bones were assessed from radiographs of the left hand and wrist after the Greulich and Pyle Atlas (1959). Median ages of attainment for bone stages were calculated using probit analysis for each stage in males and females separately. Results Maturity data for stages of the phalanges, metacarpals, carpals and radius and ulna in males and females are presented. Median ages in females were earlier compared to males for all stages. These results are largely earlier than previously published findings or where these could be calculated. Conclusion These results of individual maturity stages of phalanges, metacarpals, carpals and the distal epiphyses of the radius and ulna are useful to assess maturity in growing individuals from Sudan.